2020
DOI: 10.1101/2020.04.02.021683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mechanosensitive Ion Channel MSL10 Potentiates Responses to Cell Swelling in Arabidopsis Seedlings

Abstract: +1 314 935-9223 14 15 16 Key words: Programmed cell death, cell swelling, hypo-osmotic, mechanosensitive, reactive 17 oxygen species 18osmotic shock, where they are thought to up-regulate rehydration-responsive genes, including 68 several enzymes that reduce levels of the plant hormone ABA (Tsugama et al., 2012; Tsugama et 69 al., 2014; Tsugama et al., 2016). Despite these many observations, it is still not clear how these 70 downstream signaling components are connected, nor how they might lead to adaptive… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…Salinity-induced EPCS expansion is reversible when seedlings are moved to media lacking NaCl, triggering a hypo-osmotic shock (Lee et al, 2019). As MSL10 plays a role in the cellular response to hypo-osmotic cell swelling (Basu and Haswell, 2020), we asked if MSL10 was also responsible for EPCS shrinking under these conditions. We found that MAPPER-GFP signal decreased in cotyledon epidermal cells 24 hr after hypo-osmotic shock ( Figure 3-figure supplement 1b ) but that this phenomenon was unaffected by the msl10-1 or msl10-3G alleles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Salinity-induced EPCS expansion is reversible when seedlings are moved to media lacking NaCl, triggering a hypo-osmotic shock (Lee et al, 2019). As MSL10 plays a role in the cellular response to hypo-osmotic cell swelling (Basu and Haswell, 2020), we asked if MSL10 was also responsible for EPCS shrinking under these conditions. We found that MAPPER-GFP signal decreased in cotyledon epidermal cells 24 hr after hypo-osmotic shock ( Figure 3-figure supplement 1b ) but that this phenomenon was unaffected by the msl10-1 or msl10-3G alleles.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanosensitive ion channel MSL10 has been well studied using electrophysiological approaches (Haswell et al, 2008; Maksaev and Haswell, 2012; Maksaev et al, 2018). Genetic analyses have attributed a variety of roles to MSL10, like the induction of Ca 2+ transients, reactive oxygen species accumulation, enhanced immune responses, and programmed cell death (Basu and Haswell, 2020; Moe-Lange et al, 2021; Basu et al, 2021), but we lack a clear understanding of how MSL10 activation leads to these downstream signaling outcomes. Studies using multiple gain-of-function MSL10 alleles found that MSL10 signaling can trigger cell death independently of ion flux (Veley et al, 2014; Zou et al, 2016; Maksaev et al, 2018; Basu et al, 2020), though it remains unknown how this occurs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasma membrane (PM) mechano-sensitive channels or components of channel complexes may be involved in the [Ca 2+ ] cyt response, mediating Ca 2+ influx. Candidates include MCA1 (Mid1-Complementing Activity1, [ 1 ]), MCA2 [ 8 ], OSCA1 (reduced hyperosmolality-induced [CA 2+ ] cyt increase1, [ 9 , 10 ]), MSL10 (MscS-like10, [ 11 ]) and DEK1 (Defective Kernel 1, [ 12 , 13 ]). Alternatively, PM Ca 2+ channels governed by PM receptor-like kinases (that may or may not be wall-associated) would be competent to elevate [Ca 2+ ] cyt [ 3 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%